Towards Robust Non-Fragile Control in Wind Energy Engineering - M. A. Ebrahim (Institute of Advanced Engineering and Science, 2017)
Blade Pitch Controller (BPC) that can cope system uncertainties is one of the most interesting topics in wind energy engineering. Therefore, this paper presents a step towards the design of robust non-fragile BPC for wind energy conversion system. The proposed approach presents all boundaries of stability region that can guarantee robust stability (RS) over a wide range of operating conditions. The proposed technique results from the complementarity of both Root-Locus and Routh-Hurwitz (RL/RH) approach. Continuous variation in the operating conditions is tackled through a new hybrid control technique based on the referential integrity of both RL/RH and Kharitonov (Kh) theorem. Simulation results confirm the effectiveness of the proposed designing approach in computing the most resilient and robust controller.